Take the 2-minute tour ×
Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free, no registration required.

I've got following problem.

There are $N$ particles in an isolated system. The equation of motion for a particle $i$ is $$m_i\ddot{\vec{x}_i}(t)=\vec{F}_i(\vec{x}_1(t),...,\vec{x}_n(t),\dot{\vec{x}_1}(t),...,\dot{\vec{x}_n}(t),t),$$

and the force has a potential

$$\vec F_i=-\nabla_{\vec{x}_{i}}V(\vec{x}_1(t),...,\vec{x}_n(t)).$$

The potential is translation-invariant.

Now, the total force is $\vec F=\sum_i \vec F_i=0$. As a proof it is stated that for an arbitrary unit vector $\vec e$ holds:

$$\vec e\cdot\vec F=-\frac{d}{d\lambda}V(\vec{x}_1(t)+\lambda\vec e,...,\vec{x}_n(t)+\lambda\vec e)|_{\lambda=0}=0.$$

This last equation I do not understand. Could anyone possibly give me a clue?

share|improve this question
add comment

2 Answers 2

up vote 1 down vote accepted

Let $\vec y_i = \vec x_i + \lambda \vec e$

You have : $\frac{dV(\vec y_1, \vec y_2, ....\vec y_n)}{d\lambda} = \sum_i \vec \nabla_iV(\vec y_1, \vec y_2, ....\vec y_n) . \frac{d \vec y_i}{d \lambda}$

( chain rule for partial derivatives)

Here $\vec \nabla_iV$ is the vector which has components $(\vec \nabla_iV)_j = \frac{\partial V}{\partial (y_i)_j}$

But : $\nabla_i V(\vec y_1, \vec y_2, ....\vec y_n)|_{\lambda=0} = \nabla_i V(\vec x_1, \vec x_2, ....\vec x_n) =- \vec F_i$

Moreover, $\frac{d \vec y_i}{d \lambda} = \vec e$, and this equality is true also for $\lambda = 0$

Finally, we have :

$$\frac{dV(\vec y_1, \vec y_2, ....\vec y_n)}{d\lambda}|_{\lambda=0} = \sum_i -\vec F_i. \vec e = - \vec F. \vec e$$

share|improve this answer
    
Thank you very much! I get it now. –  fallingEntropy Jul 21 '13 at 10:17
add comment

The term $\lambda\vec e$ added to each argument in the potential is just a translation under which the potential is known to be invariant. So the derivative must be zero.

But if you use the chain rule for partial derivatives you get the result $\vec e\cdot\vec F$ and this can only be zero for all $\vec e$ if $\vec F$ is zero

This gives conservation of momentum, not conservation of force.

share|improve this answer
    
Thank you! Yes, I actually meant conservation of momentum, you are right. –  fallingEntropy Jul 21 '13 at 10:17
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.